Analysis of hospitality waste generation: Impacts of services and mitigation strategies - Eugenio Diaz-Farina; Juan José Díaz-Hernández; Noemi Padrón Fumero (Annals of Tourism Research Empirical Insights, 2023)
Municipal waste generated by hospitality has become a significant sustainability challenge for tourist destinations. Ambitious sectoral actions to mitigate waste generation will require changes in the hospitality businesses' internal operations combined with costly municipal waste services transformation. We estimate the impact of hospitality services and mitigation strategies on mixed-waste generation. Results reveal that impacts differ according to the meal plans offered and that mixed-waste generation is higher in apartments than in hotels due to the accommodation and structural services nature. Notably, employee training is found to have a greater prevention effect than alternative waste management strategies. We advocate profound changes in municipal waste charge design and provide guidelines to facilitate engagement, underlining opportunities for cooperation between policymakers and hospitality managers.
Keywords: 330; Food services; Hospitality industry; Sustainability; Tourism impacts; Waste generation; Waste mitigation strategies